Analysis of Career Development at Perum Perhutani KPH Sumedang - Ginanzar, Arif; Henriawan, Desan; Amanda, Helles (SINTESA, 2024)
The primary issue in this study is that Perum Perhutani KPH Sumedang's career development program is not the best due to staff management practices.The purpose of this study is to execute career development at Perum Perhutani KPH Sumedang, as well as to identify challenges and solutions. In order to acquire data for this study, qualitative research methods like observation, interviews, and documentation are used. Purposive sampling is the sample approach used, and there can be up to seven research informants. Data collection, data reduction, data visualization, and conclusion drawing/verification are analysis approaches. The study's findings clarify how Perum Perhutani KPH Sumedang has implemented career development, citing as factors mentors and sponsors, recognition from peers, devotion to the organization, and satisfied work performance.